The persuasive appeal of the travel vlog series "Juju on the Go" a content and netizens' comment analysis - Egay, Judea Marie C.; Felerca, Kristyl Joy P.; Ocmeja, Amor Dale G. (College of Communication, Art, and Design , University of the Philippines Cebu, 2023)
The study focuses on Filipino celebrity influencer, Julia Barreto, and her YouTube travel series, Juju On The Go, which showcases various Philippine provinces. The study analyzes the visual attributes concerning the attraction factors present in Barretto's vlogs and messaging techniques and the value of rewards in netizens' media engagements and interactivity through comments, using Social Exchange Theory (SET) and AIDA Theory. The study found that Barreto's vlogs effectively showcase destinations' cultural, economic, and natural aspects, with themes such as gastronomy, business, nature, and leisure activities. While the vlogs excel in creating awareness and acceptability, there is room for improvement in addressing affordability. Netizens engage actively with the content, influencing travel decisions, mainly through views, likes, and comments, with the attention phase gaining the highest number in the AIDA category. Finally, netizens prefer natural destination vlogs over the other two destination types. In conclusion, celebrity influencer travel vlogs are potent tools for promoting tourism, influencing consumer decisions, and building trust with the audience. This study provides valuable insights for marketers and content creators using travel vlogs for destination promotion, highlighting the significance of celebrity marketing in the digital age for guiding consumer choices and promoting local destinations.